Midterm outcomes of mitral valve repair in rheumatic heart disease - Rimy Prashad; Madhur Kumar; Nootan Hadiya; Anubhav Gupta (Heart India)
Background: Surgeons in developing nations face high load of rheumatic heart disease with mitral involvement. Although, the ongoing inflammatory activity may predispose to failure of repair and need for reoperation. But at the same time repair provides freedom from anticoagulation. It is better in preserving left ventricular function and improves chances of survival. This study aims to evaluate the mid-term outcomes of mitral valve repair in rheumatic mitral valve regurgitation, emphasizing its effect on left ventricular dimension and function. Materials and Methods: 41 patients underwent repair from July 2018- January 2023, identified from the medical record system of our centre. Out of 41, 8 patients were lost to follow up. The inclusion criteria were patients with severe rheumatic MR with or without tricuspid valve disease. Finally, 30 patients who met the inclusion criteria were enrolled in this study. Baseline characteristics and echocardiography parameters were evaluated and analysed during follow-up. Results: During follow-up, overall survival was 100%. Of the 30 patients who underwent repair, one had moderate regurgitation in the immediate post-operative period. After a mean follow up of 38months (range 69months-12 months), significant reduction in mean diastolic gradient from 16.38 mmHg to 3.1 mmHg (P < 0.001). Additionally, LVESD and LVEDD significantly reduced from 37.79 to 34.1 mm and 53.59 mm to 44.97 mm (P < 0.001), respectively was seen. Statistically significant improvement was observed in left ventricle function (P= 0.0003). Conclusion: Mid term outcome of repair are promising and encouraging in rheumatic population.